2020
DOI: 10.4103/jpbs.jpbs_119_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green tea extract mouthrinse and probiotic mouthrinse on salivary pH in a group of schoolchildren: An in vivo study

Abstract: A BSTRACT Aim and Objective: The aim of the study was to assess the efficacy of probiotic and green tea mouthrinse on salivary pH. Materials and Methods: This study was conducted over a period of 1 month among 40 healthy schoolchildren aged between 6 and 8 years. The subjects who fulfilled inclusion criteria were selected and randomly divided into two groups, namely probiotic and green tea groups. Salivary pH was recorded at baseline (0 day) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Significant increase in salivary pH was noticed in probiotic group at both recall visits, which agrees with many previous reports. 44,45 Probiotics might influence the composition of saliva, such as the concentrations of mucins and salivary immunoglobulins, thereby affecting the nature and amount of saliva secreted. The major limitation of the present study was lack of long term follow up to document the sustained effects of probiotics for periodontal therapy.…”
Section: Ta B L Ementioning
confidence: 99%
“…Significant increase in salivary pH was noticed in probiotic group at both recall visits, which agrees with many previous reports. 44,45 Probiotics might influence the composition of saliva, such as the concentrations of mucins and salivary immunoglobulins, thereby affecting the nature and amount of saliva secreted. The major limitation of the present study was lack of long term follow up to document the sustained effects of probiotics for periodontal therapy.…”
Section: Ta B L Ementioning
confidence: 99%
“…[ 13 14 ] Study conducted on forty healthy school children aged between 6 and 8 years has shown an increase in salivary pH from 6.15 to 7.65 after rinsing with green tea and reduced incidence of dental caries. [ 15 ] Currently, use of green tea dark chocolate combination is gaining popularity for prevention of dental plaque and consequent dental caries; however, the role of green tea in the prevention and progression of dental caries is still unclear and requires more evidence-based trials to be carried out. [ 16 ]…”
Section: The Effects Of Green Tea On Oral and Periodontal Healthmentioning
confidence: 99%
“…Green tea was able to create a pH balance to promote oral health on children [21]. Similarly, rinsing oral cavity with green tea significantly enhanced the mean pH values in healthy children [22]. However, it remains unclear whether another variety of tea, black tea, may also affect oral health particularly saliva.…”
Section: Introductionmentioning
confidence: 99%